NEW RECORD OF EURYCOMA APICULATA A.W. BENN (SIMAROUBACEAE) FROM FOREST RESERVE OF KENEGERIAN RUMBIO, RIAU, INDONESIA - Zulfahmi, Zulfahmi; Aryanti, Ervina; Rosmaina, Rosmaina (Research Center for Biology-Indonesian Institute of Sciences, 2019)
During extensive field surveys in the 2015 year, Eurycoma apiculata A.W. Benn has been found for the first time in the forest reserve of Kenegerian Rumbio, Kampar District of Riau province. This finding is a new record of the medicinal plant in Indonesia. The taxonomic description and photographs of the species are given in this article.